MNEs and climate change: Implications for future research. (1st September 2017) - Ivanaj, Silvester; Ivanaj, Vera; McIntyre, John R.; Guimarães da Costa, Nuno
Abstract: The goals of this opening paper of the Special Issue are threefold: First, it offers a brief review of the relevant extant literature on the drivers and barriers affecting climate change and the impacts of the organizational changes of MNEs required to face challenges posed by climate change. Then, it provides a comprehensive outline of the papers included in this Special Issue. The papers included in this Special Issue develop a range of topics, such as the contextual factors that influence the design of MNEs' strategies and practices related to climate change, interconnected and critical barriers to MNEs' green business models, the indirect effects of climate change impacts on MNEs, a multilevel framework for assessing strategic organizational responses to climate change, sustainable innovation practices developed by MNEs, and determinants and long-term performance outcomes of corporate carbon strategies, to mention a few. Finally, it proposes some potential avenues for future research.